PROFITABILITAS, UKURAN PERUSAHAAN, KINERJA LINGKUNGAN, PERTUMBUHAN PENJUALAN DAN LEVERAGE PADA PENGUNGKAPAN ISLAMIC CORPORATE SOCIAL REPORTING - Vika Fitranita; Indah Oktari Wijayanti (JAF (Journal of Accounting and Finance), 2020)
The purpose of this study is to examine the effect of profitability, company size, environmental performance, sales growth and leverage on the disclosure of Islamic Corporate Social Reporting. The population in this study are all companies listed on the Sharia Securities List during 2016-2018. The sample is determined by purposive sampling technique so that and data are analyzed using descriptive statistics and multiple linear regression analysis. Based on the partial test results show that profitability has no significant effect on the disclosure of Islamic Corporate Social Reporting (ICSR). Company size has no significant effect on the disclosure of Islamic Corporate Social Reporting (ICSR). The company's sales growth has no significant effect on the disclosure of Islamic Corporate Social Reporting (ICSR). The company's environmental performance has a significant effect on the disclosure of Islamic Corporate Social Reporting (ICSR) and leverage has a significant effect on the disclosure of Islamic Corporate Social Reporting (ICSR).